Climate change and ocean acidification outweigh local stressors in Mediterranean mussels: A multi-method convergence analysis - Andrea Gaion; Patrizia Guidi; Guido Scatena; Davide Sartori; Gianluca Bontà Pittaluga; Ombretta Spinelli; Susanna Dell’Ira; Lorenzo Pacciardi; Mara Palumbo; Margherita Bernardeschi; Giada Frenzilli; Anna Maria De Biasi (Environmental Pollution, 2026)

Assessment of mycotoxin exposure in women undergoing assisted reproduction: A study of urinary biomarkers related to oocyte and embryo development - Antonella Mastrorocco; Michele Spinelli; Nicola Antonio Martino; Daniele Ferri; Giorgio Maria Baldini; Dario Lot; Lusilla Gambacorta; Carolina Fontanarosa; Michele Solfrizzo; Maria Carmela Ferrante; Fiorenza Minervini; Domenico Baldini; et al. (Reproductive Toxicology, 2026)

Chemical characterization of weathered polyethylene microplastics in marine coastal waters using OPLS-DA technique and ATR FT-IR spectra - Matilda Mali; Rosa Ragone; Valentina Petrelli; Elhussein Mohamed Fouad Mourad Hussein Ahmed; Vito Gallo; Piero Mastrorilli; Maria Michela Dell'Anna (Marine Pollution Bulletin, 2026)

Correction: Unprecedented Mediterranean Sea warming in 2024: analysis of the driving mechanisms - Ernesto Napolitano; Adriana Carillo; Roberto Iacono; Maria Vittoria Struglia; Alessandro dell’Aquila; Massimiliano Palma; Salvatore Marullo; Eleonora De Sabata; Andrea Bordone; Gianluca Eusebi Borzelli (Frontiers in Marine Science, 2026)

A summer in Scandinavia: the travel itinerary and botanical collections of the botanist and ethno-anthropologist Stéphen Sommier in Norway in 1879 - Daniele Viciani; Irene Viviani; Lorella Dell’Olmo; Maria Gloria Roselli; Lorenzo Lastrucci (Plant Biosystems, 2026)
Stéphen Sommier (1848–1922) was a renowned botanist, plant collector, ethno-anthropologist, geographer, and photographer. He made a very significant contribution to botany during the second half of the nineteenth century. He is best known for his scientific expeditions to Italy, Scandinavia, Russia and the Caucasus. This study provides a detailed reconstruction of the travel and collection itinerary of his journey to Norway in the summer of 1879. This voyage was of botanical importance, with several specimens collected whose presence and identification have been verified by us in the Herbarium Centrale Italicum (FI). A detailed map of the 1879 itinerary and an updated floristic list are provided here. The latter also includes a list of plants that were previously unknown and were collected on a previous voyage by Sommier in 1878. The voyage is also significant from an ethnological perspective, as Sommier collected ethnological artefacts and information, and made drawings and photographs of the Sami people at that time. The places visited have been georeferenced and presented on a topographical map, highlighting the routes travelled and the sites where Sommier collected his specimens. This information will also be useful for historians, scientists and natural history museum curators working on Scandinavian flora and vegetation, ethnography, the history of photography and landscapes.

Cervical disc disease in whippets: Results of an online survey involving Italian owners and breeders - Diletta Dell'Apa; Ezio Bianchi; Luigi Auletta; Mariaelena de Chiara; Fabiana Micieli; Francesco Ferrari; Barbara Lamagna; Maria Pia Pasolini (Research in Veterinary Science, 2026)

Digital information and data flow management for building envelope solutions: the MEZeroE BIM dataset tool as an Open Innovation Service - Marta Maria Sesana; Graziano Salvalai; Paolo Dell’Oro; Akshit Gupta (Energy and Buildings, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Mentalis, DAO, and Platysma Muscles Treatment Using Botulinumtoxin A: A Multidisciplinary Italian Consensus Based on Literature Review - Salvatore Piero Fundarò; Giovanni Brunelli; Maria Cazzulani; Guido Dalla Costa; Roberto Dell’Avanzato; Roberta D’Emilio; Carlo Di Gregorio; Antonella Franceschelli; Paola Molinari; Monica Renga; Giovanni Salti; Adriano Santorelli; et al. (Toxicon, 2026)

A comprehensive analysis of inspection and audit reports in animal-derived food production by local competent authorities: A study from Emilia-Romagna, Italy (2020–2024) - Alfonso Rosamilia; Maria Luisa Bartczak; Claudia Travaglio; Silvia Vianello; Stefano Benedetti; Francesca Vergani; Marco Pierantoni; Antonio Poeta; Chiara Guarnieri; Daniele Fabbri; Giovanni Dell’Orfano; Paolo Gandolfi; et al. (Food Control, 2026)

Synthesis and characterization of silica-encapsulated phase change materials derived from waste cooking oil - Damiano Rossi; Irene Anguillesi; Alessia Iennaco; Maria Stella Leone; Piero Mastrorilli; Maria Michela Dell'Anna; Maurizia Seggiani (Chemical Engineering Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Building life cycle assessment and digital technologies: A bibliometric and systematic literature review and recent advances on their integration to boost the decarbonization of the construction sector - Marta Maria Sesana; Paolo Dell’Oro; Graziano Salvalai; Helena Gervasio (Energy and Buildings, 2026)

Transcriptomic profile of cumulus cells isolated from cumulus-oocyte complexes of prepubertal and adult sheep - Nicola Antonio Martino; Letizia Temerario; Francesco Parisi; Luigi Mansi; Luisa Bogliolo; Antonella Mastrorocco; Federica Ariu; Andrea Podda; Elena Ciani; Caterina Manzari; Ernesto Picardi; Graziano Pesole; et al. (Theriogenology, 2026)

Unprecedented Mediterranean Sea warming in 2024: analysis of the driving mechanisms - Ernesto Napolitano; Adriana Carillo; Roberto Iacono; Maria Vittoria Struglia; Alessandro dell’Aquila; Massimiliano Palma; Salvatore Marullo; Eleonora De Sabata; Andrea Bordone; Gianluca Eusebi Borzelli (Frontiers in Marine Science, 2025)
The Mediterranean Sea has experienced pronounced warming over the past few decades, but since 2022 this trend has accelerated markedly, culminating in 2024, the hottest and most dynamically energetic year of the last four decades. Record-high sea surface temperatures (SSTs) were observed across both the Western and Eastern subbasins. This study examines the spatio-temporal variability of the 2024 temperature anomaly and its driving mechanisms using satellite observations of SST and sea level, surface fluxes from atmospheric reanalysis, Citizen Science in-situ coastal data, and ocean reanalysis products from the Copernicus Marine Service. Following the strong ocean heat uptake during summer 2023, a prolonged phase of reduced ocean-to-atmosphere heat loss maintained SSTs well above climatology through autumn 2023 and winter–spring 2024. In February 2024, SSTs exceeded 15°C in the Western Mediterranean and nearly 18°C in the Eastern basin. During summer 2024, the Eastern Mediterranean underwent an exceptional marine heatwave, with surface temperatures reaching about 29°C by late August. This anomaly was mainly driven by intense air–sea heat fluxes acting on an unusually shallow mixed layer, which amplified upper-ocean heat storage and persistence. Altimeter and model data reveal that 2024 also marked a sharp increase in mean and eddy kinetic energy (EKE), particularly in the Algerian, Northwestern, and Levantine basins, where the strongest SST anomalies were observed. We found that basin-scale geostrophic kinetic energy has increased markedly from 1993 to 2024, with 2024 standing out as an exceptionally energetic year that deviates from the long-term linear trend. Overall, 2024 represents a year of exceptional oceanic conditions in the Mediterranean, with a strong link between the surface warming and enhanced oceanic kinetic energy.

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Effects of Wharton's jelly mesenchymal stromal/stem cells-derived conditioned medium and platelet-rich plasma on in vitro induced equine endometrial inflammation - Chiara Del Prete; Giulia Gaspari; Michal Andrzej Kosior; Barbara Merlo; Eleonora Iacono; Consiglia Longobardi; Nicola Antonio Martino; Maria Elena Dell’Aquila; Sara Damiano; Natascia Cocchia; Bianca Gasparrini; Anna Lange-Consiglio (Theriogenology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Bacterial Diversity of Marine Biofilm Communities in Terra Nova Bay (Antarctica) by Culture‐Dependent and ‐Independent Approaches - Melissa Bisaccia; Elisa Binda; Gabriella Caruso; Maurizio Azzaro; Ombretta Dell' Acqua; Andrea Di Cesare; Ester Maria Eckert; Flavia Marinelli (Environmental Microbiology, 2025)
Applying both culture‐independent and ‐dependent approaches, bacterial diversity of marine biofilm communities colonising polyvinyl chloride panels submerged in Terra Nova Bay (Ross Sea, Antarctica) was investigated. Panels were deployed in two sites subjected to a different degree of anthropogenic impact (Road Bay [RB] impacted site and Punta Stocchino [PTS] control site). Biofilm samples were collected after 3 or 12 months to evaluate both short‐ and long‐term microbial colonisation. Taxonomic composition of the microbial community was studied by 16S rRNA gene amplicon sequencing. Proteobacteria was the predominant phylum, followed by Bacteroidetes , Actinobacteria , Verrucomicrobia and Firmicutes . Impacted RB biofilms were found to contain a relevant fraction of potentially pathogenic bacterial genera, accounting for 27.49% of the whole community. A total of 86 psychrotolerant bacterial strains were isolated from the biofilm samples using culture‐dependent techniques designed to enrich in Actinobacteria . These strains were assigned to three different phyla: Actinobacteria (54.65%), Firmicutes (32.56%) and Proteobacteria (12.79%). 2.73% of genera identified by metabarcoding were recovered also through cultivation, while 11 additional genera were uniquely yielded by cultivation. Functional screening of the isolates revealed their hydrolytic and oxidative enzyme activity patterns, giving new insights into the metabolic and biotechnological potential of microbial biofilm communities in Terra Nova Bay seawater.

The fate of post-use biodegradable PBAT-based mulch films buried in agricultural soil - Fabiana Convertino; Sabrina Carola Carroccio; Maria Cristina Cocca; Sandro Dattilo; Anna Chiara Dell'Acqua; Luca Gargiulo; Luca Nizzetto; Paolo Maria Riccobene; Evelia Schettini; Giuliano Vox; Domenico Zannini; Pierfrancesco Cerruti (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Structural properties and microbial diversity of the biofilm colonizing plastic substrates in Terra Nova Bay (Antarctica) - Maria Papale; Stefano Fazi; Maila Severini; Roberta Scarinci; Ombretta Dell'Acqua; Maurizio Azzaro; Valentina Venuti; Barbara Fazio; Enza Fazio; Vincenza Crupi; Alessia Irrera; Carmen Rizzo; et al. (Science of The Total Environment, 2024)

Use of coenzyme Q-10 to improve the pregnancy rate in sheep - Stella Maris Teobaldo Tironi; Luan Sitó-Silva; Beatriz Lippe de Camillo; Renan Denadai; Adrielly Lais Alves da Silva; Camila de Paula Freitas-Dell’Aqua; José Antonio Dell’Aqua Junior; Rogério Antonio de Oliveira; Maria Inês Lenz Souza; Eunice Oba (Animal Reproduction Science, 2024)

Postural adjustments and perceptual responses of Nordic running: concurrent effects of poles and irregular terrain - André Ivaniski-Mello; Diana Maria Cubillos-Arcila; Stefano Dell’Anna; Lucas de Liz Alves; Flávia Gomes Martinez; Cosme Franklim Buzzachera; Jonas Alex Morales Saute; Leonardo Alexandre Peyré-Tartaruga (European Journal of Applied Physiology, 2024)
Purpose In the natural environment, humans must continuously negotiate irregular and unpredictable terrain. Recently, the poles have been extensively used during trial running events. However, we know little about how humans adjust posture and bilateral coordination to use poles in irregular terrain. Here, we compared kinematics, bilateral coordination and perceptual responses between regular (compact dust) and irregular terrain (medium-length grass) during running at preferred speed with and without poles. Methods In this transversal observational study, thirteen young healthy adults (8 men; mean ± SD; age 29.1 ± 8.0 years, body mass 76.8 ± 11.4 kg; height 1.75 ± 0.08 m) were evaluated during running at a self-selected comfortable speed with and without poles on regular and irregular terrains. Results Our results show that, despite more flexed pattern on lower-limb joints at irregular terrain, the usage of poles was not enough to re-stabilize the bilateral coordination. Also, the perceived exertion was impaired adding poles to running, probably due to more complex movement pattern using poles in comparison to free running, and the invariance in the bilateral coordination. Conclusion Besides the invariability of usage poles on bilateral coordination and lower-limb kinematics, the runners seem to prioritize postural stability over lower limb stiffness when running in medium-length grass given the larger range of ankle and knee motion observed in irregular terrain. Further investigations at rougher/hilly terrains will likely provide additional insights into the neuromotor control strategies used to maintain the stability and on perceptual responses using poles during running.

Dynamical downscaling of CMIP6 scenarios with ENEA-REG: an impact-oriented application for the Med-CORDEX region - Alessandro Anav; Marta Antonelli; Sandro Calmanti; Adriana Carillo; Franco Catalano; Alessandro Dell’Aquila; Roberto Iacono; Salvatore Marullo; Ernesto Napolitano; Massimiliano Palma; Giovanna Pisacane; Gianmaria Sannino; et al. (Climate Dynamics, 2024)
In the framework of the coordinated regional modeling initiative Med-CORDEX (Coordinated Regional Climate Downscaling Experiment), we present an updated version of the regional Earth System Model ENEA-REG designed to downscale, over the Mediterranean basin, the models used in the Coupled Model Intercomparison Project phase 6 (CMIP6). The regional ESM includes coupled atmosphere (WRF), ocean (MITgcm), land (Noah-MP, embedded within WRF), and river (HD) components with spatial resolution of 12 km for the atmosphere, 1/12° for the ocean and 0.5° for the river rooting model. For the present climate, we performed a hindcast (i.e. reanalysis-driven) and a historical simulation (GCM-driven) over the 1980–2014 temporal period. The evaluation shows that the regional ESM reliably reproduces the mean state, spatial and temporal variability of the relevant atmospheric and ocean variables. In addition, we analyze the future evolution (2015–2100) of the Euro-Mediterranean climate under three different scenarios (SSP1-2.6, SSP2-4.5, SSP5-8.5), focusing on several relevant essential climate variables and climate indicators for impacts. Among others, results highlight how, for the scenarios SSP2-4.5 and SSP5-8.5, the intensity, frequency and duration of marine heat waves continue to increase until the end of the century and anomalies of up to 2 °C, which are considered extreme at the beginning of this century, will be so frequent to become the norm in less than a hundred years under the SSP5-8.5 scenario. Overall, our results demonstrate the improvement due to the high-resolution air–sea coupling for the representation of high impact events, such as marine heat waves, and sea-level height.

In vitro exposure to PM2.5 of olfactory Ensheathing cells and SH-SY5Y cells and possible association with neurodegenerative processes - Antonio Cristaldi; Gea Oliveri Conti; Rosalia Pellitteri; Valentina La Cognata; Chiara Copat; Eloise Pulvirenti; Alfina Grasso; Maria Fiore; Sebastiano Cavallaro; Paola Dell’Albani; Margherita Ferrante (Environmental Research, 2024)

MiR-126 and miR-146a as Melatonin-Responsive Biomarkers for Neonatal Brain Ischemia - Maria Cristina Albertini; Tania Vanzolini; Serafina Perrone; Michael D. Weiss; Giuseppe Buonocore; Valentina Dell’Orto; Walter Balduini; Silvia Carloni (Journal of Molecular Neuroscience, 2023)
Despite advances in obstetric and neonatal care, challenges remain in early identification of neonates with encephalopathy due to hypoxia-ischemia who are undergoing therapeutic hypothermia. Therefore, there is a deep search for biomarkers that can identify brain injury. The aims of this study were to investigate the serum and brain expressions of two potential biomarkers, miR-126/miR-146a, in a preclinical model of hypoxia-ischemia (HI)–induced brain injury, and to explore their modulation during melatonin treatment. Seven-day-old rats were subjected to permanent ligation of the right carotid artery followed by 2.5 h hypoxia (HI). Melatonin (15 mg/kg) was administered 5 min after HI. Serum and brain samples were collected 1, 6 and 24 h after HI. Results show that HI caused a significant increase in the circulating levels of both miR-126 and miR-146a during the early phase of ischemic brain damage development (i.e. 1 h), with a parallel and opposite pattern in the ischemic cerebral cortex. These effects are not observed 24 h later. Treatment with melatonin restored the HI-induced effects on miR-126/miR-146a expressions, both in the cerebral cortex and in serum. We conclude that miR-126/miR-146a are promising biomarkers of HI injury and demonstrate an associated change in concentration following melatonin treatment.

Proposal of multimodal computed tomography-based scoring system in prediction of hemorrhagic transformation in acute ischemic stroke - Nada Elsaid; Guido Bigliardi; Maria Luisa Dell’Acqua; Laura Vandelli; Ludovico Ciolli; Livio Picchetto; Giuseppe Borzì; Riccardo Ricceri; Roberta Pentore; Stefano Vallone; Stefano Meletti; Ahmed Saied (Acta Neurologica Belgica, 2023)

The lipidomic profiles of donkey semen present greater diversity and abundance than horse semen - Maria Manoela C Chaves; Igor F Canisso; Carlos Ramires Neto; Camila de Paula Freitas-Dell'Aqua; Marco Antonio Alvarenga; Fabiana F Souza; Jose Antonio Dell'Aqua (Journal of Equine Veterinary Science, 2023)

Life Cycle Assessment of UV-C based treatment systems for the removal of compounds of emerging concern from urban wastewater - Bruno Notarnicola; Giuseppe Tassielli; Pietro Alexander Renzulli; Rosa Di Capua; Francesco Astuto; Giuseppe Mascolo; Sapia Murgolo; Cristina De Ceglie; Maria Lucia Curri; Roberto Comparelli; Massimo Dell'Edera (Science of The Total Environment, 2023)

Journal Club - Andreas Seiffert-Störiko; Khadija Aichane; Daniela Kruck; Maria Dell; Johannes Sander; Kirsten Jung; Ute Römling; Hannah Barz (BIOspektrum, 2022)

Journal Club - Yvonne Mast; Nadja Patenge; Michael Pester; Andreas Seiffert-Störiko; Volkmar Braun; Andreas Diepold; Johannes Sander; Maria Dell; Christoph Meier; Patrick Mester; Daniela Kruck; Felix Kreissl; et al. (BIOspektrum, 2022)

Evolution of LNAPL contamination plume in fractured aquifers - Simone Mineo; Filippo Maria Luigi Dell’Aera; Maria Rizzotto (Bulletin of Engineering Geology and the Environment, 2022)
The LNAPL contamination affecting an industrial area of southeastern Sicily (Italy) is reported herein as a case study to analyze some peculiarities on its spatial evolution. The free-phase product of light hydrocarbons, leaked from a tank, deserved investigations due to its anomalous migration trend, which was not consistent with the static groundwater flow direction of the area. The collection of geological and hydrogeological data and their organization into a GIS database allowed reconstructing the evolutionary stage of the plume within the 2014–2020 time interval, providing some explanation to the scientific problem. The supernatant thickness was compared with the groundwater oscillation, leading to consideration on the aquifer typology. The causes of the peculiar migration trend were found in three main factors, among which the geological and geostructural ones gain a key relevance. Achieved results show that the rock mass fracturing and the presence of underground structures, probably of tectonic origin, are responsible in driving the contamination plume through a preferential path under the dynamic condition induced by anthropic activities. This supports the need of underground geological and geostructural knowledge when dealing with similar issues and when designing specific remediation measures; the case study presented herein demonstrates that the correct location of remedial measures is crucial for reclamation purposes. Furthermore, data were statistically analyzed looking for a relation between real and apparent supernatant thickness. Prediction equations, for a quick estimation of the contamination entity in such type of aquifers, are presented providing hints for future studies on other settings worldwide.

Trends and potential human health risk of trace elements accumulated in transplanted blue mussels during restoration activities of Flekkefjord fjord (Southern Norway) - Marco Parolini; Sara Panseri; Federico Håland Gaeta; Luciana Rossi; Matteo Dell’Anno; Federica Ceriani; Beatrice De Felice; Trond Rafoss; Francesco Arioli; Salvatore Pilu; Luca Maria Chiesa (Environmental Monitoring and Assessment, 2022)
The monitoring of contaminants represents a priority to preserve the integrity of marine ecosystems, as well as to plan and to manage restoration activities in order to protect environmental and human health. In the present study, a 6-months active biomonitoring was performed to explore the levels of eighteen trace and toxic elements, including heavy metals (TEs; i.e. Al, As, Ca, Cd, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Ni, P, Pb, Sr, Ti, and Zn), accumulated in soft tissues of blue mussel ( Mytilus edulis Linnaeus, 1758) individuals transplanted at different depths (5- and 15-m depth) in five locations within the Flekkefjord fjord (Southern Norway). As this area suffered a long-lasting contamination due to both organic and inorganic contaminants, a series of restoration activities were activated to tackle and to prevent potential risks for ecosystem and local population. Our results demonstrated that the levels of TEs accumulated in edible tissues of transplanted mussels in the Flekkefjord fjord were generally low before the beginning of the restoration activities. However, location- and time-specific differences in the accumulation of TEs were noted after the implementation of such activities. Interestingly, the levels of Fe and Mn significantly increased after the beginning of the restoration activities, likely because the release of these TEs from the slag used in such operations and/or resuspension of contaminated sediments. However, assuming that native mussels can accumulate the same TEs at levels measured in transplanted individuals, our results suggest a substantial safety for human consumption of native mussels from the Flekkefjord fjord, regardless of restoration activities.

Assessing the Biological Value of Soluble Organic Fractions from Tomato Pomace Digestates - Andrea Manfredini; Antonella Chiariotti; Enrico Santangelo; Emanuela Rossi; Gianluca Renzi; Maria Teresa Dell’Abate (Journal of Soil Science and Plant Nutrition, 2021)

Ochratoxin A affects oocyte maturation and subsequent embryo developmental dynamics in the juvenile sheep model - Maria Elena Dell’Aquila; Shafaq Asif; Letizia Temerario; Antonella Mastrorocco; Giuseppina Marzano; Nicola Antonio Martino; Giovanni Michele Lacalandra; Bernard AJ Roelen; Augusto Carluccio; Domenico Robbe; Fiorenza Minervini (Mycotoxin Research, 2021)
The genotoxic and nephrotoxic mycotoxin Ochratoxin A (OTA) has also been reported to have adverse effects on oocyte maturation and embryo development. Previous studies on the effects of OTA on female fertility have used micromolar concentrations, but no information is available to date on effects in a more relevant nanomolar range. This study used a juvenile sheep model to evaluate the effects of oocyte exposure to low levels of OTA on maturation, fertilization, and embryo development. Further, it was investigated whether different mechanisms of action of OTA could be responsible for varying toxic effects at different levels of exposure. Cumulus-oocyte-complexes (COCs) were exposed to 10 μmol/L–0.1 nmol/L OTA during in vitro maturation and evaluated for cumulus viability, oocyte maturation, and bioenergetic/oxidative status. COCs were subjected to in vitro fertilization, embryo culture, and embryo quality assessment via morphology, viability, bioenergetic/oxidative status, and time-lapse monitoring. At micromolar concentrations, OTA induced cytotoxic effects, by reducing cumulus expansion and oocyte maturation. OTA altered temporospatial dynamics of zygote pronuclear formation and embryo morphokinetics. Blastocysts, even morphologically normal, were found to undergo collapse events, which were probably related to boosted blastocyst mitochondrial activity. At nanomolar concentrations, OTA did not affect COC morpho-functional parameters, but impaired oocyte ability to prevent polyspermy and increased blastocyst apoptosis. In conclusion, in the female germ cell, cytotoxic nonspecific effects characterize OTA-induced toxicity at high exposure levels, whereas fine tuning-mode effects, not associated with altered cell viability and integrity, characterize OTA toxic action at low levels.

Beauvericin alters the expression of genes coding for key proteins of the mitochondrial chain in ovine cumulus-oocyte complexes - Antonella Mastrorocco; Elena Ciani; Luigi Nicassio; Bernard A. J. Roelen; Fiorenza Minervini; Maria Elena Dell’Aquila (Mycotoxin Research, 2021)

Middle cerebral artery ischemic stroke and COVID-19: a case report - Guido Bigliardi; Ludovico Ciolli; Giada Giovannini; Laura Vandelli; Maria Luisa Dell’Acqua; Giuseppe Maria Borzì; Livio Picchetto; Francesca Rosafio; Riccardo Ricceri; Stefano Meletti (Journal of NeuroVirology, 2020)

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

Iron stains on paper. Can electrophoretic removal become an effective alternative to chemical cleaning? - Emanuele Dell’Aglio; Susanne Heidi Plattner; Maria Pia Sammartino; Giovanni Visco; Luigi Campanella (Natural Product Research, 2019)

Plumage microbiota covaries with the major histocompatibility complex in blue petrels - Sarah Leclaire; Maria Strandh; Gaia Dell’Ariccia; Marianne Gabirot; Helena Westerdahl; Francesco Bonadonna (Molecular Ecology, 2019)
To increase fitness, a wide range of vertebrates preferentially mate with partners that are dissimilar at the major histocompatibility complex (MHC) or that have high MHC diversity. Although MHC often can be assessed through olfactory cues, the mechanism by which MHC genes influence odour remains largely unclear. MHC class IIB molecules, which enable recognition and elimination of extracellular bacteria, have been suggested to influence odour indirectly by shaping odour‐producing microbiota, i.e. bacterial communities. However, there is little evidence of the predicted covariation between an animal's MHC genotype and its bacterial communities in scent‐producing body surfaces. Here, using high‐throughput sequencing, we tested the covariation between MHC class IIB genotypes and feather microbiota in the blue petrel ( Halobaena caerulea ), a seabird with highly developed olfaction that has been suggested to rely on oduor cues during an MHC‐based mate choice. First, we show that individuals with similar MHC class IIB profiles also have similar bacterial assemblages in their feathers. Then, we show that individuals with high MHC diversity have less diverse feather microbiota and also a reduced abundance of a bacterium of the genus Arsenophonus , a genus in which some species are symbionts of avian ectoparasites. Our results, showing that feather microbiota covary with MHC, are consistent with the hypothesis that individual MHC genotype may shape the semiochemical‐producing microbiota in birds.

Ambra1 Shapes Hippocampal Inhibition/Excitation Balance: Role in Neurodevelopmental Disorders - Annalisa Nobili; Paraskevi Krashia; Alberto Cordella; Livia La Barbera; Maria Concetta Dell’Acqua; Angela Caruso; Annabella Pignataro; Ramona Marino; Francesca Sciarra; Filippo Biamonte; Maria Luisa Scattoni; Martine Ammassari-Teule; et al. (Molecular Neurobiology, 2018)

Identifying Toxic Impacts of Metals Potentially Released during Deep-Sea Mining—A Synthesis of the Challenges to Quantifying Risk - Chris Hauton; Alastair Brown; Sven Thatje; Nélia C. Mestre; Maria J. Bebianno; Inês Martins; Raul Bettencourt; Miquel Canals; Anna Sanchez-Vidal; Bruce Shillito; Juliette Ravaux; Magali Zbinden; et al. (Frontiers in Marine Science, 2017)

Changes in the activity and abundance of the soil microbial community in response to the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) - Alessandro Florio; Anita Maienza; Maria Teresa Dell’Abate; Silvia Rita Stazi; Anna Benedetti (Journal of Soils and Sediments, 2016)

A lectin-based cell microarray approach to analyze the mammalian granulosa cell surface glycosylation profile - Gianluca Accogli; Salvatore Desantis; Nicola Antonio Martino; Maria Elena Dell’Aquila; Peter Gemeiner; Jaroslav Katrlík (Glycoconjugate Journal, 2016)

Glycoproteomic studies of IgE from a novel hyper IgE syndrome linked to PGM3 mutation - Gang Wu; Paul G. Hitchen; Maria Panico; Simon J. North; Mohamed-Ridha Barbouche; Daniel Binet; Howard R. Morris; Anne Dell; Stuart M. Haslam (Glycoconjugate Journal, 2016)

Microbial dynamics after adding bovine manure effluent together with a nitrification inhibitor (3,4 DMPP) in a microcosm experiment - Anita Maienza; Erland Bååth; Silvia Rita Stazi; Anna Benedetti; Stefano Grego; Maria Teresa Dell’Abate (Biology and Fertility of Soils, 2014)

Multi-methodological investigation of kunzite, hiddenite, alexandrite, elbaite and topaz, based on laser-induced breakdown spectroscopy and conventional analytical techniques for supporting mineralogical characterization - Manuela Rossi; Marcella Dell’Aglio; Alessandro De Giacomo; Rosalba Gaudiuso; Giorgio Saverio Senesi; Olga De Pascale; Francesco Capitelli; Fabrizio Nestola; Maria Rosaria Ghiara (Physics and Chemistry of Minerals, 2014)

Receptor crosstalk: haloperidol treatment enhances A2A adenosine receptor functioning in a transfected cell model - Maria Letizia Trincavelli; Serena Cuboni; Mario Catena Dell’Osso; Roberto Maggio; Karl-Norbert Klotz; Francesca Novi; Anna Panighini; Simona Daniele; Claudia Martini (Purinergic Signalling, 2010)

An atmosphere–ocean regional climate model for the Mediterranean area: assessment of a present climate simulation - Vincenzo Artale; Sandro Calmanti; Adriana Carillo; Alessandro Dell’Aquila; Marine Herrmann; Giovanna Pisacane; Paolo M. Ruti; Gianmaria Sannino; Maria Vittoria Struglia; Filippo Giorgi; Xunqiang Bi; Jeremy S. Pal; et al. (Climate Dynamics, 2010)

Re-orientation in clock-shifted homing pigeons subjected to a magnetic disturbance: a study with GPS data loggers - Anna Gagliardo; Maria Savini; Angelo De Santis; Giacomo Dell’Omo; Paolo Ioalè (Behavioral Ecology and Sociobiology, 2009)

The N-glycolyl form of mouse sialyl Lewis X is recognized by selectins but not by HECA-452 and FH6 antibodies that were raised against human cells - Junya Mitoma; Tatsuo Miyazaki; Mark Sutton-Smith; Misa Suzuki; Hideo Saito; Jiunn-Chern Yeh; Takehiro Kawano; Ole Hindsgaul; Peter H. Seeberger; Maria Panico; Stuart M. Haslam; Howard R. Morris; et al. (Glycoconjugate Journal, 2009)

Nitrogen and carbon mineralisation of leather meal in soil as affected by particle size of fertiliser and microbiological activity of soil - Maria Teresa Dell'Abate; Anna Benedetti; Alessandra Trinchera; Daniele Galluzzo (Biology and Fertility of Soils, 2003)

Thermal analysis in the evaluation of compost stability: a comparison with humification parameters - Maria Teresa Dell'Abate; Stefano Canali; Alessandra Trinchera; Anna Benedetti; Paolo Sequi (Nutrient Cycling in Agroecosystems, 1998)